Morphologic Factors Predict Pain Relief Following Pancreatic Head Resection in Chronic Pancreatitis Description of the Chronic Pancreatitis Pain Relief (CPPR) Score. Issue 4 (April 2021) - Bachmann, Kai; Melling, Nathaniel; Groteluschen, Rainer; Fleischauer, Anne; Reeh, Matthias; Ghadban, Tarik; Bockhorn, Max; Izbicki, Jakob R.
Abstract : Objective: This study analyzes the clinicopathologic findings and their impact on outcome of patients so as to identify which patients benefit most from surgical treatment in chronic pancreatitis, especially in regard to pain relief. Summary Background Data: The predominant symptom of chronic pancreatitis is chronic pain resulting in reduced quality of life. It is well known that the main reason for development of the disease is abuse of alcohol and nicotine, but only little data on factors influencing outcome are available. Methods: One thousand one hundred forty-six consecutive patients who underwent surgery for chronic pancreatitis were included. Clinicopathologic data, including morphology of the pancreas in preoperative diagnostics and the histopathologic results, were evaluated. A long-term follow-up including Quality of Life and pain scores was performed. Additionally, we describe the novel Chronic Pancreatitis Pain Relief Score (CPPR-Score) as a tool for prediction of pain relief. Results: Overall the rate of pain relief was 79.8% after surgery. The presence of an inflammatory mass in the pancreatic head larger than 4 cm ( P < 0.001), presence of a dilated main pancreatic duct of over 4 mm ( P < 0.001), histopathologically detected severe calcifications ( P = 0.001) and severe fibrosis ( P < 0.001) as well as ethanol induced disease ( P < 0.001) found to be strong independent prognostic factors for pain relief. The CPPR-Score (0–5 points) proved to be a very good predictive score for pain-relief ( P < 0.001). Conclusions: The rate of pain relief after surgical treatment in chronic pancreatitis is high and the commonly used procedures can be performed with acceptable morbidity and mortality. The Chronic Pancreatitis Pain Relief Score allows identifying patients who will benefit most from surgery.